The development KIT of science practicum for photosynthesis material to build the junior high school students’ science process skills - S Suansah; Taufik Rahman; M Muslim (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The learning process in the education unit must be organized interactively, inspiring, fun, challenging, motivating learners to actively participate, as well as providing sufficient space for learners. Currently research on the development of Practicum KIT is indispensable for transforming the educational paradigm from partial to holistic. This research is an introductory study to develop science laboratory KIT for photosynthetic materials to build students ' science process skills. The type of research conducted is research and development (RnD) with the Borg and Gall development models. The study used the first and second steps of the three steps to be taken. The activity begins with a preliminary study conducted in one of the schools involving several students and teachers. The results of this study showed that science study of photosynthetic materials has not used learning media because of the limitations of the laboratory tools and materials. Students and teachers need a science laboratory KIT for photosynthesis material as a new breakthrough in learning. By using science laboratory KIT in learning, it is expected to build students ' science process skills.